Geochemistry of landscapes of the historical area of Krister’s Hill (Kyiv) - Сплодитель Анастасія Олегівна; Сорокіна Людмила Юріївна; Голубцов Олександр Григорович; Кураєва Ірина Володимирівна (Київський національний університет імені Тараса Шевченка, 2022)
The study presents the results of ecological and geochemical research of landscapes of the historical area of Krister Hill in Podilsk district of Kyiv. The research aims to identify the current state of pollution of this territory by heavy metals - their content in the components of the landscapes (soils, plants, water environment). The paper characterizes the landscape structure and modern use of the territory. The degree of soil contamination in the sampling points located within the forest-steppe landscapes of the loess-like plain and mixed coniferous forest landscapes is characterized of the moraine-woodland plain was analyzed. For the analysis, the total pollution index (Zc) was used, according to which the study area as a whole has a moderately dangerous level of contamination of soils with heavy metals. The largest part belongs to lead and copper, the content of which in some samples is 2-4 times higher than the maximum allowable concentrations. The content of zinc and nickel is also significant. The total pollution of soils with heavy metals within the landscapes of forest plains is somewhat higher than in moraine-water-glacial landscapes. The results of a study of the microelement composition of the Krister hill vegetation indicate that the plants are characterized by an increased content of manganese, titanium, copper, and lead. Plants with a high ability to accumulate heavy metals include maple, common shingle, and lilac. To analyze the content of pollutants in surface and ground waters, water samples were taken from natural and artificial reservoirs, as well as from the bureaus. An excess of heavy metals content of tens and hundreds of times was detected in the Krister Hill water bodies. Hydrogeochemical peculiarities of drinking groundwater were established. The pump room water meets the requirements of DSTU. Excess of maximum permissible concentrations was detected for the total concentration of sodium and potassium ions and permanganate acidity. The obtained results are essential for substantiating the location of the network of complex environmental and geochemical monitoring and will contribute to the effectiveness of measures to improve the state of the natural environment and improve the living conditions of the population.

Викладено результати еколого-геохімічного дослідження ландшафтів історичної місцевості Гірка Крістера, що у Подільському районі м.Києва. Метою дослідження є виявлення сучасного стану забруднення цієї території важкими металами – їхнього вмісту у компонентах ландшафтів (ґрунтах, рослинах, водному середовищі). Охарактеризовано ландшафтну структуру та сучасне використання території. Проаналізовано ступінь забруднення ґрунтів у точках пробовідбору, що розміщені у межах лісостепових ландшафтів лесової рівнини та мішанолісових ландшафтів моренно-воднольодовикової рівнини. Для аналізу використано сумарний показник забруднення (Zc), за яким територія дослідження у цілому має помірно-небезпечний рівень забруднення ґрунтів важкими металами. Найбільша частка належить свинцю та міді, вміст яких в окремих зразках у 2-4 рази перевищує гранично допустимі концентрації. Значний також вміст цинку та нікелю. Сумарне забруднення важкими металами ґрунтів у межах ландшафтів лесових рівнин є дещо вищим, ніж у моренно-воднольодовикових ландшафтах. Результати вивчення мікроелементного складу рослинності Гірки Крістера свідчать, що рослини характеризуються підвищеним вмістом марганцю, титану, міді та свинцю. До рослин з високою здатністю акумулювати важкі метали належать клен гостролистий, щириця звичайна та бузок. Для аналізу вмісту забруднюючих речовин в поверхневих та підземних водах відбиралися зразки води з природних та штучних водойм, а також з бювету. У водоймах Гірки Крістера виявлено перевищення вмісту важких металів в десятки та сотні разів. Встановлено гідрогеохімічні особливості питних підземних вод. Бюветна вода відповідає вимогам ДСТУ. Перевищення гранично допустимих концентрацій виявлено для сумарної концентрації іонів натрію і калію та для перманганатної окиснюваності. Отримані результати є важливими для обґрунтування розміщення мережі комплексного еколого-геохімічного моніторингу, сприятимуть підвищенню ефективності заходів поліпшення стану природного середовища та покращення умов проживання населення.
Геохімія ландшафтів історичної місцевості Гірка Крістера (м. Київ)
Keywords: еколого-геохімічні дослідження; ландшафти; забруднення; важкі метали; грунти; рослинність; водне середовище; ecological and geochemical research; landscapes; pollution; heavy metals; soils; plants; water environment